Collaborative communication strategy between Diskominfo and Biro ADPIM in managing BEJA as West Java Vision implementation - Rahardjo, Muthia Khairunnisa; Sutarjo, Moch. Armien Syifaa (Jurnal Ilmiah Komunikasi Makna, 2025)
This study analyzes the collaborative communication strategies between the West Java Communication and Information Agency (Diskominfo Jabar) and the West Java Bureau of Administration and Leadership (Biro Adpim Jabar) in managing the Bewara Jawa Barat (BEJA) program to support the vision of West Java Province. Using a qualitative approach and descriptive method through observation and interviews, the study refers to Cutlip and Center’s four-step public relations strategy model: defining the problem, planning, implementation, and evaluation. The results show that collaboration between the two agencies is effective at every stage. In the problem-definition phase, internal teams are formed to facilitate communication and task division. The planning stage focuses on issues relevant to news value and public interest. Implementation is carried out through the BEJA platform using well-managed communication strategies. Evaluation is conducted internally and externally to assess performance and public response. The consistently collaborative communication strategy makes BEJA a model of integrated and responsive public communication.